Music and death : interdisciplinary readings and perspectives - Bennett, Marie Josephine; Gracon, David (Emerald interdisciplinary connexions, 2019)
Music is often our companion when dealing with the incomprehensibility of loss. This edited collection speaks to the multifarious and complex ways in which music accompanies, supplements, and complements aspects of death and dying, whether this is the death of a loved one, or a celebrity from popular culture.